Correlation and path coefficient analysis for yield and quality traits under organic fertilizer management in rice (Oryza sativa L.) - Dhurai S. Y., D. Mohan Reddy And Pradeep Kumar Bhati (Electronic Journal of Plant Breeding, 2014)
An investigation was carried out in 32 rice genotypes to understand the association among fourteen contributing traits for yield and quality and their direct and indirect influence on the grain yield under organic fertilizer management. The correlation analysis indicated that genotypic correlation coefficient was higher than phenotypic correlation coefficient and grain yield was significantly associated with harvest index, number of grains per panicle and days to maturity. Path coefficient analysis revealed that kernel elongation ratio, kernel length, kernel L/B ratio, kernel breadth, days to maturity, harvest index, panicle length and plant height had positive direct effect on grain yield. Hence, selection based on these traits could help to bring simultaneous improvement of yield and quality traits.